The Impact of Brand Awareness, Brand Association, Brand Perceived Quality toward Repurchase Intention Mediated by Brand Loyalty in the Case of ZARA - Valerie Vania Santoso; Fetricia Magdalena Bunanta (iBuss Management, 2019)
Repurchase intention is one of the most critical factor that can increase company’s profitability and create sustainable growth. There are some ways to increase consumer’s repurchase intention, and one of the way is by having the right branding strategy. Thus, this research is conducted in order to investigate the influence of brand awareness, brand association, and brand perceived quality on brand loyalty and repurchase intention in the case of ZARA as ZARA has proven to be able to survive in such tight competition and maintain its position as the most well-known fashion brand. This study used quantitative research and self-administered questionnaire as the research instrument with a sample data set of 97 respondents. The data will be analyzed by using blue classical assumption test, multiple regression test, and Sobel test to test the impact of the variables. The findings indicate that brand awareness and brand perceived quality has a positive and insignificant influence on brand loyalty and repurchase intention. However, brand association has been proven to have a positive and significant influence on brand loyalty and repurchase intention. Furthermore, the mediating variable which is brand loyalty also has been proven to exert a positive and significant influence on repurchase intention. Keywords: Brand Awareness, Brand Association, Brand Perceived Quality, Brand Loyalty, Repurchase Intention